Новый вид и определительная таблица палеоарктических наездников рода Barylypa (Hymenoptera, Ichneumonidae) - Атанасов, А.З. (Вестник зоологии, 1975)
An identification key is compiled of paleoarctic species Barylypa with the exception of B. formosa Schm. and B. rossica Hellen, the types of which were not studied by the author. A species B. torquata sp. n. is described by the materials from several points of the Soviet Union. This species differs from the other species of the genus by the presence of the longitudinal columns on the last tergites of the abdomen, by the intercalary segment strongly stretched almost up to the apex of posterior coxas, by yellow-white spots on the abdomen apex and by the parameres acuminate on the apex in males.